Analysis of the Performance of the Liquid Cooling System on the Thermal Efficiency of Honda Vario 125 Motorcycle - Kiki Dwi Putra Mahariyanto; Habib Rinaldy; Subayu Siburian; Fardin Hasibuan; Oloan Ritonga; Ilham Safi'i; Tanto Suharjo (Universitas Riau Kepulauan, 2026)
This study discusses the performance of the liquid cooling system on the Honda Vario 125 motorcycle to understand its effect on the thermal efficiency of the engine during operation. The liquid cooling system plays a role in keeping the engine temperature stable, so that the combustion process takes place more effectively. The test was carried out by taking data on cylinder head temperature, coolant temperature, and fuel consumption at various engine rev levels. The data obtained is analyzed to assess the ability of the cooling system to reduce temperature rise and keep the engine at an optimal working range. The results show that at medium to high cycles, liquid cooling systems are able to maintain temperature stability with relatively small fluctuations. These more stable thermal conditions contribute to improved combustion efficiency which is reflected in decreased specific fuel consumption and increased thermal efficiency. These findings indicate that the cooling system design on the Honda Vario 125 has adequate capabilities to maintain consistent engine performance, especially in daily use with load variations. This study can be a technical reference in the development of motor vehicle cooling systems.